Assessment of the BMI among 8–12-year-old School Students Stratified by Socioeconomic Status from Multan, Pakistan: A Cross-sectional Study - Syed Ghufran Hadier; Medad Ali Sibtain; Liu Yinghai; Syed Muhammad Zeeshan Haider Hamdani; Syed Danish Hamdani (Journal of Management Practices, Humanities and Social Sciences, 2023)
Addressing a gap in existing research, this study investigates the correlation between socioeconomic status and body mass index among 8-to-12-year-old in Multan, Pakistan. It offers insights into obesity trends in a developing country context, highlighting economic disparities' role in childhood obesity. This cross-sectional study, a component of the PAK-IPPL project focusing on Multan, was conducted during the 2020–2021 academic year across higher secondary schools in Multan division. We employed stratified random sampling for participant selection. Using Cochran's formula, the sample size was calculated to be 1360 across three divisions, with 455 participants specifically from Multan. Anthropometric data were collected to calculate body mass index, and analysis was performed using IBM SPSS 22, encompassing descriptive statistics, Independent samples t-tests, chi-squared tests, ANOVA, and Tukey's HSD test. The study revealed no significant gender differences in age, height, body weight, and body mass index among the children. However, boys showed significantly higher waist circumferences than girls (60.29 ± 9.55 cm vs. 57.38 ± 8.03 cm, p < 0.05). SES was found to significantly influence body weight and Body Mass Index, with higher SES linked to increased values. Notably, children from higher SES backgrounds had an average weight of 35.31 kg (± 8.84) and BMI of 18.06 kg/m² (± 3.80). The combined effect of SES, gender, and age accounted for approximately 14% of the variance in childhood obesity. Positive correlations were observed between body mass index and weight, and waist circumference, varying according to SES and weight categories. The study highlights a significant correlation between higher SES and increased body weight and BMI, underscoring the importance of socioeconomic factors in understanding and combating childhood obesity. These findings call for targeted public health initiatives that account for socioeconomic and demographic factors. The insights provided are valuable for future research and interventions aimed at reducing obesity in children.